TEACHING RELIGIOUS AND SECULAR KNOWLEDGE - Alieva Nilufar Kochkarovna (American Journals, 2023)
In this article, Mahmudhoja Behbudi emphasizes that the role of education in the development of society is extremely large, and writes, "A nation without the benefit of modern science and technology will become a burden to other nations." Enlightenment activities, his work for the development of schools and education among the Jadids, his contribution to the rise of the Jadid press, and his promotion of enlightenment through publicist articles in the press are covered.
Keywords: jadid, Mahmudhoja Behbudi, enlightenment, press, publicism, school of new method.